When transparency is opaque: Effects of diacritic marks and vowel letters on dyslexic Hebrew readers. (October 2016) - Weiss, Yael; Katzir, Tami; Bitan, Tali
Abstract: The current study examined the effects of orthographic transparency and familiarity on brain mechanisms involved in word recognition in adult dyslexic Hebrew readers. We compared functional Magnetic Resonance Imaging (fMRI) brain activation in 21 dyslexic readers and 22 typical readers, and examined the effects of diacritic marks that provide transparent but less familiar information and vowel letters that increase orthographic transparency without compromising familiarity. Dyslexic readers demonstrated reduced activation in left supramarginal gyrus (SMG) as compared to typical readers, as well as different patterns of activation within the left inferior frontal gyrus (IFG). Furthermore, in contrast to typical readers, dyslexic readers did not show increased activation for diacritics in left temporo-parietal junction regions, associated with mapping orthography to phonology. Nevertheless, both groups showed the facilitation effect of vowel letters on regions associated with lexical-semantic access. Altogether the results suggest that while typical readers can compensate for the reduced familiarity of pointed words with increased reliance on decoding of smaller units, dyslexic readers do not, and therefore they show a higher cost.